The Relationship of Erythrocyte Distribution Width Value with Mortality in Patients with COVID-19 Pneumonia - Ayşe Vahapoğlu; Ülkü Aygen Türkmen (Galenos Yayinevi, 2022)
Objective: Patients with coronavirus disease-2019 (COVID-19) pneumonia have high hospitalization, intensive care unit (ICU) need and mortality rates. In this study, we aimed to follow-up the need of intensive care and mortality rates in patients with COVID-19 pneumonia with red blood cell distribution width (RDW) value because it is a cheap and easyl accesible marker. Materials and Methods: Patients with severe COVID-19 pneumonia hospitalized in the ICU (n=162), patients with mild COVID-19 pneumonia hospitalized in the ward (n=163), and healthy individuals (healthcare workers without a history of COVID-19 pneumonia) (n=162) were included in the study. Hemoglobin (HGB), white blood cell (WBC), red blood cell and RDW values were determined from the first admission hemogram and their effect on mortality was evaluated retrospectively. Results: When the groups were compared according to mortality, the average age of the patients who died of COVID-19 was found to be higher. According to the age-adjusted model analysis, in our study, in which the risk factors affecting mortality were investigated, RDW value was not found to be effective on mortality. Also age, HGB, WBC and COVID-19 positivity were found to be statistically significant parameters on mortality. Conclusion: Rapid and easily accessible markers are needed to reduce the follow-up of patients with severe COVID-19 pneumonia with high mortality in the ICU. In our study, while the effect of hematological parameters such as WBC and HGB on mortality was significant, it was observed that the RDW value did not affect mortality. Prospective randomized studies are needed in this regard.